MANAJEMEN STRATEGI LEMBAGA DALAM MENINGKATKAN PELAYANAN NASABAH DI BMT KOTA BANDAR LAMPUNG - Mubasit; Husaini (Institut Agama Islam Agus Salim Metro Lampung, 2021)
This study aims to find out how the Institutional Strategic Management in Improving CustomerService at Bmt Bandar Lampung City. The research approach used is a qualitative approach.While this type of research is field research. Sources of research data are BMT Leaders,Employees and Customers. Methods of data collection is done by observation, interviews anddocumentation. The data processing method in this study was obtained through researchinstruments in four stages, namely: data reduction, data presentation, data verification andtriangulation. The results of this study indicate that: The strategy carried out by BMT BandarLampung City in improving services to members is a functional strategy. Functional strategy isa strategy that is managed by each function of the company's organization in the hope ofcreating better competition with BMT competitors, so that it will increase competitiveadvantage. Management Management strategy in supporting customer or member satisfaction,the BMT tries to add office facilities, communicates good relations with members, carries out apick-up system for customers, carries out a professional human resource recruitment process.Indicators of the quality of service performance in BMT Bandar Lampung City, as follows: 1)Physical Appearance Indicators (Tangible), 2) Reliability Indicators (Reliability), 3)Responsiveness Indicators (Responsivenes), 4) Competence Indicators (Competence), 5)Indicators of Credibility (Credibility), 6) Indicators of Courtesy (Courtessy), 7) Indicators ofSecurity (Security), 8) Indicators of Access (Access), 9) Indicators of Communication(Communication), 10) Indicators of Understanding (Understanding the customer).